2016
DOI: 10.1177/0160017615603577
|View full text |Cite
|
Sign up to set email alerts
|

Regional Labor Market Performance in Europe

Abstract: The labor market effects of the recent financial and economic crisis are rather heterogeneous across countries and regions. Such differences in labor market performance among industrialized countries are an issue of ongoing research. The objective of this article is to analyze labor market disparities among European regions and to provide evidence on the factors behind these differences. Whereas previous research focused on the effects of national labor market institutions, we also take structural characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…They found substantial gains from this policy in terms of reducing the unemployment rate and increasing the participation rate. Herwartz and Niebuhr () found that a substantial part of regional disparities regarding unemployment rate can be attributed to wage bargaining legislation, an effect also found by Longhi et al (). Che and Spilimbergo () argue that labour market reforms can spur regional convergence if more flexibility is introduced.…”
Section: Introductionmentioning
confidence: 69%
“…They found substantial gains from this policy in terms of reducing the unemployment rate and increasing the participation rate. Herwartz and Niebuhr () found that a substantial part of regional disparities regarding unemployment rate can be attributed to wage bargaining legislation, an effect also found by Longhi et al (). Che and Spilimbergo () argue that labour market reforms can spur regional convergence if more flexibility is introduced.…”
Section: Introductionmentioning
confidence: 69%